1991
DOI: 10.1037/0021-9010.76.6.863
|View full text |Cite
|
Sign up to set email alerts
|

Models of supervisory job performance ratings.

Abstract: Proposed and evaluated in this research were causal models that included measures of cognitive ability, job knowledge, task proficiency, two temperament constructs (achievement and dependability), awards, problem behavior, and supervisory ratings. The models were tested on a sample of 4,362 U.S. Army enlisted personnel in nine different jobs. Results of LISREL analyses showed partial confirmation of Hunter's (1983) earlier model, which included cognitive ability, job knowledge, task proficiency, and ratings. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
148
1
5

Year Published

1994
1994
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(163 citation statements)
references
References 40 publications
9
148
1
5
Order By: Relevance
“…22, respectively, to .35 and .41. Recent efforts to model job performance have begun to clarify the role of g. Path models of training and job proficiency (mostly in military jobs) indicate that g strongly predicts success in training and acquiring job knowledge, which in turn strongly predict task proficiency (Borman, White, Pulakos, & Oppler, 1991;Borman, Hanson, Oppler, Pulakos, & White, 1993;Borman, White, & Dorsey, 1995;Hunter, 1983;Ree, Carretta, & Teachout, 1995;Schmidt, Hunter, & Outerbridge , 1986).…”
Section: Illustrative Correlational Datamentioning
confidence: 99%
“…22, respectively, to .35 and .41. Recent efforts to model job performance have begun to clarify the role of g. Path models of training and job proficiency (mostly in military jobs) indicate that g strongly predicts success in training and acquiring job knowledge, which in turn strongly predict task proficiency (Borman, White, Pulakos, & Oppler, 1991;Borman, Hanson, Oppler, Pulakos, & White, 1993;Borman, White, & Dorsey, 1995;Hunter, 1983;Ree, Carretta, & Teachout, 1995;Schmidt, Hunter, & Outerbridge , 1986).…”
Section: Illustrative Correlational Datamentioning
confidence: 99%
“…Although causal modeling yields the direct, indirect, and total effects of predictors on criteria (given certain assumptions that art often difficult to meet), the variables are usually observed measures, and researchers are typically not interested in the observed measures themselves. The Hunter (1983Hunter ( , 1986, Schmidt et al (1986), and Borman et al (1991) efforts just described all corrected the variables fo~r attenuation. Removing the measurement error from the variables is one way of approximating the modeling of latent variables, but this procedure makes the implicit assumption that removing measurement error yields a measure of the construct that is neither contaminated nor deficient--an assumption that might not be justified.…”
Section: S~mentioning
confidence: 99%
“…Finally, Borman, White, Pulakos, and Oppler (1991) applied the Hunter performance model to data from Project A and compared it to an expanded model that included multiple components of performance assessed via ratings, as well as non-cognitive predictor information (i.e., achievement orientation and dependability). Borman et al found the expanded model accounted for over twice as much variance in supervisor ratings as Hunter's model.…”
Section: S~mentioning
confidence: 99%
“…Granted, work sample performance measures are high fidelity measures of "can-do" aspects of job performance (versus "will-do" aspects, see Borman et al, 1995;Borman, White, Pulakos, & Oppler, 1991;DuBois, Sackett, Zedeck, & Fogli, 1993;Motowidlo, Borman & Schmit, 1997;Motowidlo & VanScotter, 1994;Sackett, Zedeck, & Fogli, 1988). However, they are not without their limitations.…”
Section: Charles E Lancementioning
confidence: 99%